Isocapnic hyperventilation provides early extubation after head and neck surgery: A prospective randomized trial. Issue 8 (19th April 2018) - Hallén, K.; Jildenstål, P.; Stenqvist, O.; Oras, J.; Ricksten, S.‐E.; Lindgren, S.
Abstract : Background: Isocapnic hyperventilation (IHV) shortens recovery time after inhalation anaesthesia by increasing ventilation while maintaining a normal airway carbon dioxide (CO2 )‐level. One way of performing IHV is to infuse CO2 to the inspiratory limb of a breathing circuit during mechanical hyperventilation (HV). In a prospective randomized study, we compared this IHV technique to a standard emergence procedure (control). Methods: Thirty‐one adult ASA I‐III patients undergoing long‐duration (>3 hours) sevoflurane anaesthesia for major head and neck surgery were included and randomized to IHV‐treatment (n = 16) or control (n = 15). IHV was performed at minute ventilation 13.6 ± 4.3 L/min and CO2 delivery, dosed according to a nomogram tested in a pilot study. Time to extubation and eye‐opening was recorded. Inspired (FICO2 ) and expired (FETCO2 ) CO2 and arterial CO2 levels (PaCO2 ) were monitored. Cognition was tested preoperatively and at 20, 40 and 60 minutes after surgery. Results: Time from turning off the vapourizer to extubation was 13.7 ± 2.5 minutes in the IHV group and 27.4 ± 6.5 minutes in controls ( P  < .001). Two minutes after extubation, PaCO2 was 6.2 ± 0.5 and 6.2 ± 0.6 kPa in the IHV and control group respectively. In 69% (IHV) vs 53% (controls), post‐operative cognition returned to pre‐operative values within 40 minutes after surgery (NS). Incidences of pain and nausea/vomiting did not differ between groups. Conclusions: In this randomized trial comparing an IHV method with a standard weaning procedure, time to extubation was reduced with 50% in the IHV group. The described IHV method can be used to decrease emergence time from inhalation anaesthesia.